Pricing Practices of Exporting and Non-Exporting Units (A Comparative Study of SSIs In Haryana) - Sharma, Reetu (Prabandhan: Indian Journal of Management, 2010)
The paper highlights the pricing practices of exporting and non exporting SSI units. It is a well known fact that Price is the only factor which generates revenue while other elements of marketing mix cause cost. It means price is a reward for factor of production in form of wages, rent, interest and profit. The paper highlights some important aspects of pricing such as pricing objectives, factor influencing price setting, pricing policies and strategies and types of discount etc. Responses obtained in this regard show that exporting and non- exporting SSI units highly prefer to target return to investment. They are not much conscious about market share and target sales. So, this reason affects the sustainability of these units. On the other hand, under pricing policies, a mix of uniform and differential policy should be adopted to get success. In addition to this, proper practices should be adopted regarding factors influencing in determining price, types of discount offered etc. So, that they are capable to get effective market share as well as target returns for their efforts.